Inpatient Patient Satisfaction Influenced By Core Service Quality And Peripheral Service Quality (Study At Dr. SOEGIRI Hospital In Lamongan Regency) - Ariefin, Mesra Surya (DiE: Jurnal Ilmu Ekonomi dan Manajemen, 2021)
This study aims to examine and analyze the effect of core service qualityand peripheral service quality on Patient Satisfaction at RSUD Dr.Soegiri Lamongan. The number of samples in this study were 36patients RSUD Dr. Soegiri Lamongan. Data collection techniques usingquestionnaires, interviews, and literature review. Analysis of the data inthis study is multiple linear regression analysis using SPSS 26 software.The results of this study indicate that core service quality and peripheralservice quality have a significant effect on Patient Satisfaction inpatientDr. Soegiri Lamongan in parallel or simultaneously